(untitled) (The Pakistan Development Review, 2022)
The University Research System In Pakistan is a thoroughly researched work, providing an extensive discussion on the state of university research in Pakistan. It highlights problems being faced by researchers and compares them with global research practices. The authors recommend reforms at the institutional level, the type of research funding, the metrics of measurement, and the adaptation and promotion of a research culture that provides incentives for teamwork and mentorship for the new entrants in the industry. Research on the barriers and possible solutions is vital for quality and problem-oriented research that produces products that can compete with global research. The authors give a diagnosis of the problems of the research in Pakistan by identifying key problem areas and their possible solutions. We can sum up the purpose of the book as follows: “The rapidly changing world has brought new challenges requiring innovative and problem-solving research. Pakistan’s university research system lacks the essentials required for competing in the modern world. Therefore, the situation necessitates exploring where the problem exists and what can be the possible solutions”.